Pain mechanisms in rheumatoid arthritis - McWilliams, Daniel F.; Walsh, David A. (Clinical and Experimental Rheumatology, 2017)
Understanding of the causes and underlying mechanisms of pain in people with RA is rapidly changing. With the advent of more effective disease modifying drugs, joint inflammation is becoming a more treatable cause of pain, and joint damage can often be prevented. However, the long-term prognosis for pain still is often unfavourable, even after inflammation is suppressed. Pain is associated with fatigue and psychological distress, and RA pain qualities often share characteristics with neuropathic pain. Each of these characteristics suggests key roles for central neuronal processing in RA pain. Pain processing by the central nervous system can maintain and augment RA pain, and is a promising target for future treatments. Inflammatory mediators, such as cytokines, may provoke central pain sensitisation in animal models, and both local and systemic inflammation might contribute to central pain augmentation in RA. Controlled trials of treatments that target central pain processing have shown some benefit in people with RA, and might be most effective in individuals for whom central pain augmentation plays a key role. For people with RA who experience persistent pain, identifying underlying pain mechanisms critically determines the balance between escalation of anti-inflammatory and disease-modifying treatments and other strategies to provide symptomatic analgesia.